2017
DOI: 10.1101/127522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topological demarcation by HMGB2 is disrupted early upon senescence entry across cell types and induces CTCF clustering

Abstract: Ageing-relevant processes, like cellular senescence, are characterized by complex, often stochastic, events giving rise to heterogeneous cell populations. We hypothesized that entry into senescence of different primary human cells can be triggered by one early molecular event affecting the spatial organization of chromosomes. To test this, we combined whole-genome chromosome conformation capture, population and single-cell transcriptomics, super-resolution imaging, and functional analyses applied on proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…For example, we showed that both CTCF and cohesin form small protein clusters 7 and a recent study found that CTCF can form large foci upon senescence, which causes genome reorganization. 74 Thus, detailed studies on the nuclear organization of CTCF and cohesin should be informative. Fifth, absolute quantification of CTCF boundary permeability (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we showed that both CTCF and cohesin form small protein clusters 7 and a recent study found that CTCF can form large foci upon senescence, which causes genome reorganization. 74 Thus, detailed studies on the nuclear organization of CTCF and cohesin should be informative. Fifth, absolute quantification of CTCF boundary permeability (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a circular polymer as a substrate not only mimics bacterial plasmids and DNA mini-rings but also stably looped genomic regions in eukaryotes. These regions may be looped by chromatin-binding proteins such as transcription factors (e.g., HMGB2 [81]) and Polymerases, but also by CTCF [59] in the case of TADs.…”
Section: Circular Polymers Mimic Plasmids or Stably Looped Genomic Re...mentioning
confidence: 99%
“…Yet, the genome is poorly represented by a 1D array of Ising spins. Instead, it is a fluctuating polymer which can assume distinct spatial organisations in 3D and also in response to stimuli [15,16] and epigenetic cues [3].…”
mentioning
confidence: 99%